2018
DOI: 10.1111/ejn.14264
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and oxidative stress in induced pluripotent stem cell models of Parkinson's disease

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease. Two percent of the population above the age of 60 is affected by the disease. The pathological hallmarks of PD include loss of dopaminergic neurons and the presence of Lewy bodies. Mitochondrial dysfunction and oxidative stress are thought to play a pivotal role in both sporadic and familial forms of the disease. In this review we focus on the role of mitochondrial dysfunction and oxidative stress in induced pluripotent stem cell (IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…The symptoms of PD are caused by a loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) resulting in a decrease of dopamine (DA) levels in the striatum. Mitochondrial dysfunction and its related oxidative stress and inflammation are common features in PD patient brain samples, PD iPSC-derived neurons, and/or PD animal models [11,12,41,42]. To note, pathological studies in the substantia nigra regions from 6 patients suggest that Complex I deficiency did not correlate with parkinsonism [43].…”
Section: Defective Mitophagy and Imbalanced Mitochondria-derived Vesimentioning
confidence: 99%
“…The symptoms of PD are caused by a loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) resulting in a decrease of dopamine (DA) levels in the striatum. Mitochondrial dysfunction and its related oxidative stress and inflammation are common features in PD patient brain samples, PD iPSC-derived neurons, and/or PD animal models [11,12,41,42]. To note, pathological studies in the substantia nigra regions from 6 patients suggest that Complex I deficiency did not correlate with parkinsonism [43].…”
Section: Defective Mitophagy and Imbalanced Mitochondria-derived Vesimentioning
confidence: 99%
“…Although the precise pathogenesis of PD still remains elusive, several studies demonstrate that mitochondrial dysfunction and oxidative damage play the important roles in PD pathogenesis [5–7]. It has been revealed that 25–30% of PD patients have significant deficiency of mitochondrial complex I and increased reactive oxygen species (ROS) levels [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies have found increased vulnerability to oxidative stress, higher levels of mtDNA damage, and impaired mitochondrial movement as a result of the G2019S mutation, indicating compromised mitochondrial function (Cooper et al, 2012, Sanders et al, 2014, Hsieh et al, 2016, Schwab et al, 2017, Bose and Beal, 2019. Mitochondrial function alterations have in turn been shown to affect the plasticity of synapses and morphology of neurites as the availability of mitochondria is both essential and limiting for the support and maintenance of these structures (Li et al, 2004).…”
Section: Unveiling Different Network Stress Responses Through Transiementioning
confidence: 99%